HE EFFECT OF THICKNESS SOLIDITY ON GROWTH AND GROWTH OF LIVES SEEDS (Polymesodaerosa) IN MANGROVE AREA PANDANG BIRIK-BIRIK VILLAGE, PARIAMAN CITY SUMATERA BARAT By: - Rafi Novendri Kaslan; Syafruddin Nasution; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in Mai - July 2019 in the mangrove area of Padang Birik-Birik Village, Pariaman City, West Sumatra. This study aims to determine the growth and survival of lokan (Polimesodeerosa) seed shells with different densities. The method used in this study is an experimental method with a completely randomized design (CRD) consisting of one factor (stocking density) with four levels of treatment namely stocking densities of 20, 40, 60 and 80 individuals / container or equivalent to 80, 160, 240 and 320, with three replications arranged randomly. The container is made of a net framed by a cubeshape d wooden cube with a length of 50 cm with an area of 250 cm or 0.25 , rate were observed in lokan seed during this study. The results showed that the best growth and survival rates were 20 (80/) stocking densities while the lowest was 80 (240/ ) stocking densities. To be cultivated in the village of Padang Birik-birik naturally can be done with stocking densities 80/and 160. Keywords: Effect of stocking density, shell growth, Polymesodaerosa, Pariaman